2018
DOI: 10.1016/j.jwb.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Building subsidiary local responsiveness: (When) does the directionality of intrafirm knowledge transfers matter?

Abstract: The present study focuses on effects of subsidiary internal knowledge-based activitiesknowledge transfer and reverse knowledge transfer-and absorptive capacity on local responsiveness. We also examine whether absorptive capacity, shared values, and psychological safety, representing constituents of the motivation-opportunity-ability model of behavior, moderate relationships of subsidiary internal knowledge-based activities with responsiveness. Based on a sample of 173 Chinese subsidiaries, the results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 130 publications
(201 reference statements)
0
28
0
Order By: Relevance
“…However, the global strategy literature has focused primarily on the issue of knowledge management, rather than understanding the specific environmental contexts in local markets or the influence of strategic orientation on knowledge management processes. Specifically, there has been little attention so far to the environment-strategyknowledge management-performance (ESKMP) linkage at the MNC subsidiary level (Vanaik and Midgley, 2019;Najafi-Tavani, Robson, Zaefarian, Andersson and Yu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the global strategy literature has focused primarily on the issue of knowledge management, rather than understanding the specific environmental contexts in local markets or the influence of strategic orientation on knowledge management processes. Specifically, there has been little attention so far to the environment-strategyknowledge management-performance (ESKMP) linkage at the MNC subsidiary level (Vanaik and Midgley, 2019;Najafi-Tavani, Robson, Zaefarian, Andersson and Yu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is because target firm employees struggle to retain their identity and may even be less efficient after the acquisition (Du & Sim, 2016). It is imperative for target firms to understand the extent to which they can absorb knowledge through their employees, as this is an acknowledged source of advantage and way of realising an acquisition's strategic intent (Cohen & Levinthal, 1990;Najafi-Tavani et al, 2018;Volberda, Foss, & Lyles, 2010). Cohen and Levinthal (1990) reported that absorptive capacity depends on the efforts of employees and the firm's ability to effectively utilise their acquired knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Achieving effective knowledge flow largely involves seamlessly transplanting knowledge into a target firm (Hurtado-Ayala & Gonzalez-Campo, 2015;Najafi-Tavani et al, 2018). Absorptive capacity is regarded as a supportive tool in the mobilisation of knowledge flow as it incorporates processes to introduce, integrate and assimilate knowledge into the firm.…”
Section: Absorptive Capacity and Knowledge Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Such risk is prevalent even for top‐level managers with well‐utilized institutional ties. Managers understand that it is the sagacious use of financial resources, not their superiority, which creates competitive advantages in emerging markets (Najafi‐Tavani, Robson, Zaefarian, Andersson, & Yu, 2018).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%